Economic Potential Analysis of Tour Package Management for Sustainable Tourism Development - Sarapang, Vinny Corylitha; Rante, Margaretha Wadid; Wahyuni, Sri (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This research analyzes the potential of tourism packages in Barru Regency, focusing on sustainable tourism development. The methodology employed involved in-depth interviews with local government officials, homestay managers, and community members to gather data on policies, challenges, and opportunities in tourism management. The key findings highlight that the local government has made significant efforts in building infrastructure and carrying out promotional activities to enhance the appeal of tourist destinations. However, homestay management faces challenges in maintaining service quality while capitalizing on the growing interest of tourists in authentic local experiences. Natural attractions and cultural diversity have also emerged as major drivers for tourist visits. The study concludes that achieving sustainable tourism development in Barru Regency requires collaboration between the government, the local community, and tourism managers. Furthermore, the research underscores the need for continued efforts to strengthen community capacity, ensuring they can effectively manage and utilize the region's tourism potential. By doing so, Barru Regency can maximize its tourism benefits while maintaining its environmental and cultural integrity.